The Influence of Learning Motivation on Reading Literacy Skills of Fifth Grade Elementary School Students - Joko Nugroho; Slamet Subiyantoro; Chumdari Chumdari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Reading literacy is an important skill in influencing students' academic success because it is the basis for mastering various knowledge. This study aims to 1) describe the level of students' learning motivation 2) determine students' reading literacy skills, 3) determine the effect of learning motivation on students' reading literacy skills. This research method uses a quantitative method with an ex-post facto design. Data collection uses questionnaire and test techniques. The questionnaire instrument is used to obtain data on students' learning motivation. The test instrument is used to obtain data on students' reading literacy skills. Data analysis techniques consist of prerequisite tests and hypothesis tests. The prerequisite tests consist of normality tests and homogeneity tests. Hypothesis testing uses a t-test with the help of the IBM SPSS Statistics 22 program. The results of this study indicate that there is an influence of learning motivation on reading literacy skills with a p value of 0.001 <0.05. The conclusion of this study confirms that learning motivation has a significant influence on the reading literacy skills of fifth grade elementary school students